Produktivitas Kerja Penyuluh Pertanian Perikanan Kehutanan dan Ketahanan Pangan Kota Tomohon (Studi Pada Penyuluhan Tanaman Padi) - Mamesah, Olfana M.; Tulusan, Femy M. G.; Londa, Very Y. (JURNAL ILMIAH SOCIETY, 2015)
Agricultural extension essentially implemented to help farmers to be able to solve the problems faced by itself. The role of agricultural extension as a facilitator, motivator and supporter of the motion of farmers is the central point in outreach to farmers. However, reality shows that agricultural extension is a member or staff of institutions such task is not uncommon in doing more work oriented to the interests of the department in the interests of farmers. In response to this, the need for extension workers who have good working productivity and maximum.By using qualitative research design in expressing and analyzing labor productivity Extension Agriculture, Fisheries, Forestry and Food Security in Tomohon in counseling rice plants was found that labor productivity Extension Agriculture, Fisheries, Forestry and Food Security in the extension of rice plants in Tomohon not yet fully based on efficiency and effectiveness. This is evident in the lack of a special FEA on food commodities, lack of budget for extension activities, no definite schedule owned by farmers on extension activities, extension when dropped spaciousness just visiting as well as any other activities in conjunction with time extension resulting in extension activities are not carried out.Keywords: Work Productivity, Extension, Rice.